Relationship Between Tree Diameter and Mangrove Vegetation Carbon Stock in Apar Village, Pariaman City, West Sumatra - Gusfi, Melly; Efriyeldi, Efriyeldi; Mulyadi, Aras (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2025)
This research was conducted in January 2024 in the Mangrove Area of ​​Apar Village, Pariaman City, West Sumatra Province. This research aims to determine mangroves' density and carbon stock conditions and the relationship between the diameter of mangrove trees of the Rhizophora mucronata, Sonneratia caseolaris, and S.alba types with mangrove carbon stock. The method used in this research is a survey method with direct observation and data collection at the research location. Non-destructive sampling measured the diameter of mangrove trees' breast height in each plot. The average density of mangrove stands at the three research stations was 1,222.22 tons/ha, the average amount of mangrove biomass was 688.49 tons/ha, the average amount of mangrove carbon stock was 323.59 tonnes/ha, and the average mangrove CO₂ uptake is 1,186.51 tons/ha